Assessing the performance of the international maritime organisation (IMO) - Lim, Foong Sian. (2011)
The International Maritime Organisation (IMO), being the only international body of its kind, has been relied upon to raise the regulatory standards in the entire shipping industry. Safety in the maritime industry has been under the scrutiny of the worldwide community ever since the unfortunate Titanic disaster. For many years, the industry has been deemed as highly risky and dangerous as significant loss of human lives can result whenever accidents occur. Without an alternative body to compare the IMO‟s performance against, there is always a lingering fear that this monopolistic power will drive it towards its own downfall. Therefore, we aim to evaluate the effectiveness and efficiency of the IMO in promoting Safety and Security of Shipping, as well as the Prevention of Marine Pollution. With more than 50 years of work to look at, we hope to generate a report card that is as far as possible, untainted by cultural and political influences. Due to limitation of time, and lack of objective information and statistics, this report can still serve as a basis for future research. With the use of extensive literature review, technical analysis, interviews and surveys with shipping professionals, qualitative and quantitative results derived provide a holistic view of the IMO‟s performance, particularly in the area of maritime safety. Indeed, the IMO has been relatively effective in raising safety standards since her inception, bearing in mind that in today‟s world, shipping is deemed to be the most regulated industry with over 5000 regulations. However the extent of actual compliance beyond ratification of the conventions reveals a big gap for improvements. Nonetheless, the general consensus holds that the IMO has scored well in maritime safety. It is thus highly recommended that the IMO continues its move towards establishing goal-based standards and looks towards leveling the playing field by urging and pressuring lax member states to enhance their degree of compliance.